2013
DOI: 10.4103/0028-3886.121920
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, functional, and psychosocial outcome after severe traumatic brain injury: A cross-sectional study at a tertiary care trauma center

Abstract: In this study 61% patients with STBI had good recovery in functional outcome and 45.4% in psychosocial outcome at 1 year follow-up. However, improvement in cognitive outcome was not so optimistic with the ability to learn new things being most affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…25 Similarly, Agrawal and colleagues recently reported continued improvement to 6 months post TBI among an Indian cohort of 58 TBI patients who were followed to 12 months, and Sinha and colleagues reported 58–61% good cognitive, functional, and psychosocial outcomes after severe TBI in 77 severe TBI patients. 24, 26 The present study, which is the largest cohort of TBI patients followed to 12 months in India documents a greater increase in good outcomes between 6 and 12 months in the absence of rehabilitation care. Differences in time of peaking of best outcomes between the current work and other studies may be explained by differences in provision of early ICU Guideline adherence, discharge GOS status and/or continued post discharge TBI care.…”
Section: Discussionmentioning
confidence: 55%
“…25 Similarly, Agrawal and colleagues recently reported continued improvement to 6 months post TBI among an Indian cohort of 58 TBI patients who were followed to 12 months, and Sinha and colleagues reported 58–61% good cognitive, functional, and psychosocial outcomes after severe TBI in 77 severe TBI patients. 24, 26 The present study, which is the largest cohort of TBI patients followed to 12 months in India documents a greater increase in good outcomes between 6 and 12 months in the absence of rehabilitation care. Differences in time of peaking of best outcomes between the current work and other studies may be explained by differences in provision of early ICU Guideline adherence, discharge GOS status and/or continued post discharge TBI care.…”
Section: Discussionmentioning
confidence: 55%
“…[14][15][16] Studies suggest that, although there may be an improvement in cognitive function two years after the moderate or severe trauma, these functions still remain impaired. 17 The QL deals with the subjective perceptions of different aspects, being of a personal and mutable nature varying according to the individual's context, interests, and values.…”
Section: Discussionmentioning
confidence: 99%
“…16 A limiting factor in this study was the small sample size that did not allow consistent conclusions in the comparison between the groups. Although the number of patients from within São Paulo was considerable, as determined by the inclusion criteria, and devised to facilitate their appearance, the sample size was small due to poor attendance.…”
Section: 10mentioning
confidence: 97%
See 1 more Smart Citation
“…Gupta and Taly [6] reported improvements in disability rating sale among 44 Indian patients with severe TBI who initiated rehabilitation services 3 months post-TBI for 1 month. Furthermore, Agrawal and Joshi [7] recently reported continued improvement to 6 months post-TBI among 58 TBI patients who were followed to 12 months, and Sinha et al [8] reported 58-61% good cognitive, functional and psychosocial outcomes in 77 severe TBI patients. In this study, TBI patients followed to 12 months in India, and it was shown a greater increase in good outcomes observed between 6 and 12 months in the absence of rehabilitation care.…”
mentioning
confidence: 99%